Practical Considerations of Applying Traceability Concepts to the Internal Quality Control Materials for Trueness Verification in Medical Laboratories - Cheng, Weizhi (Journal of Medical Biochemistry, 2024)
Traceability is an important tool in the harmonization and standardization of reporting laboratory results, making them comparable across measurement systems. Driven by ISO 15189 accreditation requirements, medical laboratories have entered the era of metrological traceability. For medical laboratories, although calibrators are a key factor in the entire metrological traceability system, there is controversy over internal quality control (IQC) materials. It has been proposed that trueness materials supplied by the system's manufacturer with metrological traceability can be used for monitoring IQC so as to confirm that the performance of the measuring system is properly unbiased. This article discusses the pros, cons, and some myths regarding the new 2022 edition of ISO 15189 standard requirements for IQC and the application of traceability in daily operations. The discussion would focus on the implementation challenges and operational hurdles of applying traceability to IQC materials for trueness verification in medical laboratories. There are practical considerations with regard to the preparation of the IQC materials. Our suggestion is that testing of available different lot numbers of the manufacturer’s end-user calibrators on a routine basis, perhaps weekly or monthly, would be much more practical and feasible, instead of testing IQC materials with metrological traceability. We must acknowledge the limitations and restrictions that manufacturers and laboratories need to face before the recommendations can be applied in routine practices.
Keywords: Quality control; Laboratory management; Analytical systems; Traceability